GAMBARAN PENGGUNAAN ALAT PERAGA BONEKA JARI DAN TANPA ALAT PERAGA DALAM PENYULUHAN TERHADAP TINGKAT PENGETAHUAN KESEHATANGIGI DAN MULUT SISWA/I KELAS IVSDNEGERI 101832 PANCUR BATUKECAMATAN PANCUR BATU - Aritonang, Netty Jojor; Siahaan, Yenny Lisbeth (Poltekkes Kemenkes Medan, 2021)
Health education is one of the health education activities, carried out by spreading a message, instilling confidence with the aim that the community aware, know, understand, and want to do a suggestion related to health. Counseling can be done by the method of storytelling, assisted by finger puppet props. This study aims to determine the level of knowledge of students about oral health through counseling - using and without finger puppets. This research is a descriptive study with survey method which examines 36 samples. Data is collected through a questionnaire filled out by students, which is then processed using a frequency distribution table Through the results of the study, the following data are known: the score of knowledge level after counseling without teaching aids is 4 students (22%) in the good category, 14 students (78%) in the medium category, and no students in the bad category; after giving information with finger puppets props changes, 15 students (83%) in the good category, 3 students (17%) in the medium category, and no students in the bad category. This study concludes that counseling with the use of finger puppets is very effective, characterized by an increase in knowledge through this extension method.